PEDAGOGY OF CARE: AFFECTIVITY AS THE CENTRAL AXIS OF LEARNING - Soares , Aline Muniz dos Santos; Sene, Aparecida Moraes Siqueira; Mancuso, Leandra Rafaella França; Dias, Sara de Oliveira; dos Santos , Luciana Américo; Gomes , Stefanni Silva; Borges, Vanessa Vieira Gomes; Braga , Wilson; Costa, Leuzeny Martins de Almeida; Barbosa, Maria Zilda da Silva; Barbosa, Maryanah Silva; França, Josiani Aparecida de Mello; et al. (Editora Impacto Científico, 2025)
This study aims to explore the theme of "Pedagogy of Care," focusing on the crucial role that affectivity plays as a central axis in learning. In an educational context where student performance and retention in schools are central issues, we analyze how care and the establishment of affective bonds contribute significantly to academic success. The research also investigates the use of educational games not only as an engagement tool but as an effective means of teaching vital social skills such as empathy, cooperation, and conflict resolution. Through a review of existing literature and the analysis of qualitative and quantitative data, this work seeks to demonstrate that pedagogical practices centered on care and affectivity are fundamental to creating more inclusive and effective learning environments where students feel emotionally supported and motivated to actively participate in the educational process. The study concludes that integrating such approaches can not only improve academic performance but also increase school retention rates, proving to be a valuable educational strategy in the contemporary context.DOI: https://doi.org/10.56238/edimpacto2025.092-039